An Analysis of Students' Ability in Writing Tourism Advertisements Located in Nias Island at SMP Negeri 1 Gido - Gulo, Restu Jaya; Zega, Riswan; Harefa, Trisman; Harefa, Afore Tahir (English Language Teaching Methodology, 2025)
This study tourism plays a significant role in promoting local culture and contributing to regional economic growth. In recent years, educational institutions have recognized the importance of integrating tourism-related topics into language learning as a way to enhance students’ communication skills while fostering cultural awareness. In the context of Nias Island, which is known for its unique traditions and natural beauty, introducing tourism advertisement writing in English can serve as a means of promoting local destinations to a wider audience. This study focuses on analyzing the ability of ninth-grade students to write tourism advertisements, highlighting both their strengths and areas that need improvement. Investigates the writing abilities of ninth-grade students at SMP Negeri 1 Gido in crafting tourism advertisements about Nias Island. Through a qualitative descriptive approach, data were collected via observations, interviews, and documentation from 32 students in class IX-A. Results reveal that students possess strong skills in identifying content and creativity (96%) but face difficulties in grammar (43%), structure (66%), and persuasiveness (66%). Limited vocabulary, underdeveloped persuasive techniques, and insufficient knowledge of local attractions hinder their writing effectiveness. The findings highlight the importance of integrating persuasive writing instruction and cultural content into English lessons to support tourism promotion.